An Acetylenic Alkaloid from the Calcareous Sponge Leucetta sp. - Nicole J. de Voogd; Idam Hermawan; Junichi Tanaka (Marine Drugs, 2011)
A new acetylenic alkaloid was isolated from the sponge Leucetta sp. The structure was established by analyzing spectroscopic data. The alkaloid showed cytotoxicity IC50 2.5 mg/mL against NBT-T2 cells.